Ekonomiczne i prawne instrumenty minimalizujące ryzyko niewypłacalności jednostek samorządu terytorialnego - Zioło, Magdalena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper presents the issue of insolvency risk of local government entities,including its determinants and legal and economic tools to used to mitigateinsolvency risk of local government entities.